2022
DOI: 10.1177/03635465211063158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Intensity Pulsed Ultrasound on the Graft-Bone Healing of Artificial Ligaments: An In Vitro and In Vivo Study

Abstract: Background: As many researchers have focused on promoting the graft-bone healing of artificial ligaments, even with numerous chemical coatings, identifying a biosafe, effective, and immediately usable method is still important clinically. Purpose: (1) To determine whether a low-intensity pulsed ultrasound system (LIPUS) promotes in vitro cell viability and osteogenic differentiation and (2) to assess the applicability and effectiveness of LIPUS in promoting the graft-bone healing of artificial ligaments in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…LIPUS promoted the cell proliferation, adherence, and osteoblastic differentiation of MC3T3-E1 preosteoblasts seeded on PET sheets. Meanwhile, in vivo study of rabbits confirmed the promoting effect of LIPUS on bone formation, and enhanced effect on graft-bone healing, such as less fibrous tissue, narrower interface, direct contact and higher ultimate failure load [121].…”
Section: Bone-ligament or Bone-tendon Repairmentioning
confidence: 81%
See 1 more Smart Citation
“…LIPUS promoted the cell proliferation, adherence, and osteoblastic differentiation of MC3T3-E1 preosteoblasts seeded on PET sheets. Meanwhile, in vivo study of rabbits confirmed the promoting effect of LIPUS on bone formation, and enhanced effect on graft-bone healing, such as less fibrous tissue, narrower interface, direct contact and higher ultimate failure load [121].…”
Section: Bone-ligament or Bone-tendon Repairmentioning
confidence: 81%
“…It was vital to design a strategy that was both effective and quickly useful for promoting graftbone healing of artificial ligaments (Table 4). Liu et al recently organized a study to investigate the effects of LIPUS on polyethylene terephthalate (PET) artificial ligament concerning cell behaviors in vitro and osseointegration in the extra-articular graft-bone healing model (Figure 7) [121]. LIPUS promoted the cell proliferation, adherence, and osteoblastic differentiation of MC3T3-E1 preosteoblasts seeded on PET sheets.…”
Section: Bone-ligament or Bone-tendon Repairmentioning
confidence: 99%